1987
DOI: 10.1200/jco.1987.5.2.260
|View full text |Cite
|
Sign up to set email alerts
|

A phase I-II study of bialkylator chemotherapy, high-dose thiotepa, and cyclophosphamide with autologous bone marrow reinfusion in patients with advanced cancer.

Abstract: Twenty patients with disseminated cancer both untreated and previously treated received bialkylator chemotherapy, thiotepa, and cyclophosphamide and reinfusion of cryopreserved autologous bone marrow (ABMR). The cyclophosphamide dose was constant at 7.5 g/m2 over three days, while thiotepa was started at 1.8 mg/kg for three days in escalating dose by a modified Fibonacci schema to 7 mg/kg. The median time to recovery of more than 500 granulocytes and more than 50,000 platelets/microL was 18 and 27 days, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 11 publications
1
8
1
Order By: Relevance
“…Grade II nausea and vomiting (observed in about 60% of the patients) and grade 11I enteritis (observed in about 80% of the patients) were the clinically relevant non-haematological toxicities of this high-dose treatment. In terms of non-haematological toxicity, these results are similar to or better than those reported elsewhere for other combinations of high-dose alkylating agents with progenitor cell support in combination or not with etoposide (Williams et al, 1987;Gaspard et al, 1988;Slease et al, 1988;Vincent et al, 1988;Eder et al, 1990;Elias et al, 1991;Williams et al, 1992;Siegert et al, 1994;Benedetti Panici et al, 1995). Our results are better in terms of non-haematological toxicity than those reported recently for patients with high-risk cancer treated with ifosfamide, carboplatin and etoposide (Barnett et al, 1993;Fields et al, 1994;Elias et al, 1995), high-dose cyclophosphamide and etoposide (de Graaf et al, 1994), high-dose cyclophosphamide and carboplatin (Spitzer et al, 1995) , the quality of the graft collected in these patients, most of whom were chemotherapy-naive at the time of PBPC mobilization and collection, made it possible to obtain an accelerated haematopoietic recovery in most patients, faster than that reported in several other experiences of PBPC transplantation (Gianni et al, 1989;Menichella et al, 1991;Elias et al, 1992;To et al, 1992;Henon et al, 1992;Sheridan et al, 1992;Peters et al, 1993b;Sica et al, 1993;Chao et al, 1993;Bensinger et al, 1993;Pierelli et al, 1994;Spitzer et al, 1994;Shimazaki et al, 1994;Bishop et al, 1994).…”
Section: Discussionsupporting
confidence: 87%
“…Grade II nausea and vomiting (observed in about 60% of the patients) and grade 11I enteritis (observed in about 80% of the patients) were the clinically relevant non-haematological toxicities of this high-dose treatment. In terms of non-haematological toxicity, these results are similar to or better than those reported elsewhere for other combinations of high-dose alkylating agents with progenitor cell support in combination or not with etoposide (Williams et al, 1987;Gaspard et al, 1988;Slease et al, 1988;Vincent et al, 1988;Eder et al, 1990;Elias et al, 1991;Williams et al, 1992;Siegert et al, 1994;Benedetti Panici et al, 1995). Our results are better in terms of non-haematological toxicity than those reported recently for patients with high-risk cancer treated with ifosfamide, carboplatin and etoposide (Barnett et al, 1993;Fields et al, 1994;Elias et al, 1995), high-dose cyclophosphamide and etoposide (de Graaf et al, 1994), high-dose cyclophosphamide and carboplatin (Spitzer et al, 1995) , the quality of the graft collected in these patients, most of whom were chemotherapy-naive at the time of PBPC mobilization and collection, made it possible to obtain an accelerated haematopoietic recovery in most patients, faster than that reported in several other experiences of PBPC transplantation (Gianni et al, 1989;Menichella et al, 1991;Elias et al, 1992;To et al, 1992;Henon et al, 1992;Sheridan et al, 1992;Peters et al, 1993b;Sica et al, 1993;Chao et al, 1993;Bensinger et al, 1993;Pierelli et al, 1994;Spitzer et al, 1994;Shimazaki et al, 1994;Bishop et al, 1994).…”
Section: Discussionsupporting
confidence: 87%
“…In comparison with previous studies on HDC with TEPA reported by others, 6,7,16,17 the frequency of severe mucositis was lower. In a phase I study of TEPA, 20 and 15% of patients with 1005-1215 mg/m 2 of TEPA exhibited severe (fatal) gastrointestinal toxicity and CNS complications, respectively.…”
Section: Discussioncontrasting
confidence: 49%
“…The current study with no fatal RRT and only grade 1-2 toxicities in the 10 patients treated at the MTD compares favorably with other regimens developed in refractory patients (Table 6). [3][4][5][6][7]49 No significant cardiac, pulmonary, renal, hepatic or central nervous system toxicities were observed in this study.…”
Section: Upnmentioning
confidence: 90%
“…1,2 Because of the success which is seen in the treatment of hematologic malignancies, high-dose chemotherapy (HDC) and autologous peripheral blood stem cell transplantation (PBSCT) is being used increasingly in patients with solid tumors where a dose-response relationship is thought to exist. [3][4][5][6][7][8] High-dose chemotherapy with autologous PBSCT has been demonstrated to produce prolonged disease-free survival in some patients with advanced breast and ovarian cancer as well as refractory testicular cancer. [9][10][11][12][13][14] Reasons for poor outcome in some studies following HDC and autologous PBSCT using currently available treatment regimens include relapse and transplant-related mortality.…”
mentioning
confidence: 99%